Mindfulness : A Practical Guide to Finding Peace in a Frantic World - Williams, Mark and Penman, Danny (London Piatkus, 2011)
Mindfulness reveals the secrets of lifelong happiness and details a unique programme developed by Oxford University psychologist Professor Mark Williams with colleagues around the world.
Include Index
Foreword by Jon Kabat-Zinn
Keywords: Mindfulness-based cognitive therapy -- Mind and body therapies -- Meditation